CORRELATION BETWEEN PSYCHOLOGICAL PARAMETERS SUCH AS DEPRESSION, ANXIETY, AND STRESS AND AFFECT SCORE AMONG MEDICAL STUDENTS - BHAGYASHREE N; KIRAN VEERAPANENI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: In the modern era, internet use has turned out to be a significant arena for day-to-day life activities. Proper use of the internet is harmless, but misuse of this tool might lead to disruptions in psychological health and social relationships, yet available reports about the association between internet use and affect are inconsistent. Hence, the objective is to assess and correlate the psychological parameters with the affect score among medical college students using the depression anxiety stress scale (DASS)-21 questionnaire and positive and negative affect schedule (PANAS) scale. Methods: The present study was a cross-sectional study conducted on medical students in the age group of 17–22 years. 150 participants were recruited by random sampling. DASS-21 scale was used to assess depression, anxiety, and stress, consisting of 21 items designed to measure emotional states of depression, anxiety, and stress. PANAS is designed to assess individuals’ positive and negative moods. Results: Pearson’s correlation of these psychological parameters with affect scores had a significant negative correlation with the positive affect score (depression [p=0.003], anxiety [p=0.01], and stress [p<0.04]) and a significant positive correlation with negative affect score (depression [p<0.02], anxiety [p=0.0009], and stress [p=0.01]). Students should be closely monitored with regard to their use of the internet, and also, internet addiction and psychological behaviors can be reduced by providing early counseling and interventional therapy. Conclusion: Awareness about the harmful effects of excessive internet use should be provided so as to enhance the academic performance of students.